Can glutathione be a biomarker for suicide risk in women 18 months postpartum? - da Silva Schmidt, Paula Michele; Trettim, Jéssica Puchalski; Longoni, Aline; Grings, Mateus; de Matos, Mariana Bonati; de Avila Quevedo, Luciana; Ardais, Ana Paula; Nedel, Fernanda; Ghisleni, Gabriele; Leipnitz, Guilhian; Pinheiro, Ricardo Tavares; de Assis, Adriano Martimbianco (Frontiers in Psychiatry, 2023)
Background: Suicide risk is prominent among the problems affecting populations, mainly due to the broad family, psychosocial and economic impact. Most individuals at suicidal risk have some mental disorder. There is considerable evidence that psychiatric disorders are accompanied by the activation of neuro-immune and neuro-oxidative pathways. The aim of the study is to evaluate the serum levels of oxidative stress biomarkers in women at risk of suicide after 18 months of postpartum. Methods: This is a case-control study, nested within a cohort study. From this cohort, 45 women (15 without mood disorders and 30 with mood disorders (Major depression and Bipolar disorder)) were selected at 18 months postpartum, the depression and suicide risk were assessed using the Mini International Neuropsychiatric Interview Plus (MINI-Plus) instrument, Module A and C, respectively. Blood was collected and stored for later analysis of the reactive species (DCFH), superoxide dismutase (SOD), and glutathione reduced (GSH). For data analysis, the SPSS program was used. To compare the nominal covariates with the outcome GSH levels, the Student's t-test or analysis of variance (ANOVA) was used. Spearman's Correlation was performed for analysis between the quantitative covariates and the outcome. To analyze the interaction between the factors, multiple linear regression was performed. Bonferroni analysis was used as an additional/secondary result to visualize differences in glutathione levels according to risk severity. After the adjusted analysis, p-values <0.05 were considered statistically significant. Results: The percentage of suicide risk observed in our sample of women at 18 months postpartum was 24.4% (n=11). After adjusting for the independent variables, only the presence of suicide risk remained associated with the outcome (β 0.173; p=0.007), low levels of GSH at 18 months after postpartum. Likewise, we verified the difference in GSH levels according to the degree of suicide risk, observing a significant association between the differences in glutathione means in the group of women with moderate to high risk compared to the reference group (no suicide risk) (p=0.009). Conclusions: Our findings suggest that GSH may be a potential biomarker or etiologic factor in women at moderate to high risk of suicide.